2011
DOI: 10.3109/14767058.2011.598587
|View full text |Cite
|
Sign up to set email alerts
|

Mode of delivery and other pregnancy outcomes of patients with documented scoliosis

Abstract: The aim of this study was to explore whether scoliosis is a risk factor for adverse obstetric outcomes and specifically for cesarean delivery (CD) and labor dystocia. Association between scoliosis and pregnancy outcome was studied before. Confounding conclusions prevent proper counseling of patients. Appropriate statistical analysis of a suitable cohort is helpful in resolving this issue. A retrospective population-based study comparing all singleton pregnancies of women with and without documented scoliosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Our results are supported by Lebel et al, who found that after accounting for nulliparity, fertility treatment, and maternal age, labor induction was not associated with scoliosis. 12 Our cohort had an overall caesarean section rate of 34.5%, which is similar to the national average (26.1%-32.9%). 17 The incidence of urgent/emergency caesarean section was 14%.…”
Section: Fig 2 Indications For Urgent/emergency Caesarean Section (supporting
confidence: 79%
“…Our results are supported by Lebel et al, who found that after accounting for nulliparity, fertility treatment, and maternal age, labor induction was not associated with scoliosis. 12 Our cohort had an overall caesarean section rate of 34.5%, which is similar to the national average (26.1%-32.9%). 17 The incidence of urgent/emergency caesarean section was 14%.…”
Section: Fig 2 Indications For Urgent/emergency Caesarean Section (supporting
confidence: 79%
“…The patient suffered from both obvious spinal protrusion of the lateral bending deformity and kyphosis with “S”-type distortion, resulting in shorter longitudinal diameter of the thoracic cavity, reduced volume of the thoracic cavity, limited expansion of the chest wall, decreased lung compliance, and severe impairment of ventilation function. [3] Consequently, in the third trimester of pregnancy, the rapid enlargement of the uterus leads to diaphragm elevation, thereby resulting in decreased total lung volume, functional residual capacity, [4] and lung reserve function. The severe pulmonary infection was probably related to the abovementioned structural changes, which was critical and could result in hypoxia and cardiopulmonary failure any time, thereby endangering the lives of both mother and fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the severe deformity, huge dorsal mass, and severe lung infection, the patient had to be placed in a special position for vaginal delivery during the second stage of labor. [4] The patient was positioned as follows: upper body was at 45° from horizontal elevation, while lying on the right lateral side, and air gasket was used to prevent oppression (Fig. 3B).…”
Section: Discussionmentioning
confidence: 99%
“…In patients who had undergone spinal fusion, progression in the unfused portion of the spine was negligible. [10] Lebel et al [11] suggested that scoliosis is not a risk factor for adverse pregnancy outcomes, and specifically labor dystocia.…”
Section: Discussionmentioning
confidence: 99%